Особливості імплементації міжнародно-правових норм у сфері праці моряків в Україні - Іванова, А. В.; Иванова, А. В.; Ivanova, А. (My University, 2013)
In the article are researched peculiarities of national law in the implementation of international labor law norms in the legal system of Ukraine regarding regulation of sailors labor. There are determined problems of realization of realization and application of mechanisms of implementation international law norms in the field of labor and social sailors sphere. It is stated on the primacy of international law over national law of Ukraine in this sphere. It is shown the necessity of the development of normative acts in Ukraine, directed on harmonization of national legislation with international law.
Іванова А. В. Особливості імплементації міжнародно-правових норм у сфері праці моряків в Україні / А. В. Іванова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 110-120.
Keywords: міжнародне трудове право; імплементація норм міжнародного трудового права у правовій системі України; регулювання праці моряків; соціальна сфера моряків; международное трудовое право; имплементация норм международного трудового права в правовой системе Украины; регулирование труда моряков; социальная сфера моряков; international labor law; implementation of international labor law in the legal system of Ukraine; regulation of seafarers; Social protection of seafarers